India, modernity and the great divergence : Mysore and Gujarat (17th to 19th c.) - Yazdani, Kaveh (Leiden ; Boston : Brill, 2017)
"India, Modernity and the Great Divergence is an original and pioneering book about India's transition towards modernity and the rise of the West. The work examines global entanglements alongside the internal dynamics of 17th to 19th century Mysore and Gujarat in comparison to other regions of Afro-Eurasia. It is an interdisciplinary survey that enriches our historical understanding of South Asia, ranging across the fascinating and intertwined worlds of modernizing rulers, wealthy merchants, curious scholars, utopian poets, industrious peasants, and skilled artisans. Bringing together socio-economic structures, warfare, techno-scientific innovations, knowledge production and transfer of ideas, this book forces us to rethink the reasons behind the emergence of the modern world"--Provided by publisher.
The transitional state of India's history of ideas, science, technology and culture in the 17th and 18th centuries -- Mysore -- Gujarat -- Epilogue: Transition from middle to late modernity -- Appendix.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Social change -- India -- History; Economic development -- India -- History; Karnataka (India) -- Civilization; Gujarat (India) -- Civilization; India -- Civilization -- European influences; India -- Civilization -- 1200-1765.; India -- Civilization -- 1765-1947.; India -- Relations -- Europe; Europe -- Relations -- India; Electronic books